Standard Operating Procedures for Female Genital Sexual Pain. (12th September 2012) - Fugl‐Meyer, Kerstin S.; Bohm‐Starke, Nina; Damsted Petersen, Christina; Fugl‐Meyer, Axel; Parish, Sharon; Giraldi, Annamaria
ABSTRACT Introduction. Female genital sexual pain (GSP) is a common, distressing complaint in women of all ages that is underrecognized and undertreated. Definitions and terminology for female GSP are currently being debated. While some authors have suggested that GSP is not per se a sexual dysfunction, but rather a localized genial pain syndrome, others adhere to using clearly sexually related terms such as dyspareunia and vaginismus. Aim. The aims of this brief review are to present definitions of the different types of female GSP. Their etiology, incidence, prevalence, and comorbidity with somatic and psychological disorders are highlighted, and different somatic and psychological assessment and treatment modalities are discussed. Methods. The Standard Operating Procedures (SOP) committee was composed of a chair and five additional experts. No corporate funding or remuneration was received. The authors agreed to survey relevant databases, journal articles and utilize their own clinical experience. Consensus was guided by systematic discussions by e‐mail communications. Main Outcome/Results. There is a clear lack of epidemiological data defining female GSP disorders and a lack of evidence supporting therapeutic interventions. However, this international expert group will recommend guidelines for management of female GSP. Conclusions. GSP disorders are complex. It is recommended that their evaluation and treatment are performed through comprehensive somato‐psychological multidisciplinary approach. Fugl‐Meyer KS, Bohm‐Starke N, Damsted Petersen C, Fugl‐Meyer A, Parish S, and Giraldi A. Standard operating procedures for female genital sexual pain. J Sex Med **;**:**–**.